Contrasting morphology with population genetics approach: An insight to revision of the Neotropical annual fish "Austrolebias robustus" species group based on a taxonomic integrative framework. (27th January 2019) - García, Graciela; Gutiérrez, Verónica; Ríos, Néstor; Serra, Sebastián; Calviño, Pablo; Duarte, Alejandro; Loureiro, Marcelo
Abstract: The objective of the present paper was to characterize the morphological and genetic patterns of variability in four taxa of the Austrolebias robustus species group distributed in two of the major southernmost river basins in South America. We compared results from the two approaches followed in this study to access hypotheses of species limits using an integrative taxonomic framework and patterns of population differentiation. Mitochondrial Cytb gene genealogy and networks analyses detected four major clades which do not fully correspond to currently known species of the A. robustus species group. Although the clade including A. robustus and A. nonoiuliensis received well support, the clade of A. cinereus also contains individuals of A. vazferreirai . BEAST analysis suggested that these taxa may have emerged from independent vicariant allopatric events. While high level of overlap was detected in all morphological analyses, in which species were distinguished only by small changes in body and head shape, the patterns of morphological variation detected among taxa were generally congruent with the different hypotheses of differentiation emerging from genetic population analyses. Based on all present results and following the principle of priority, we propose that A. vazferreirai is a junior synonym of A. cinereus . The subtle morphological discrimination among these taxa, representing local adaptations, reinforces the need to implement urgent actions in order to preserve the A. cinereus population, only reported since its description for the type locality in the PLPUB region. Our results are relevant and informative, supporting the implementation of biodiversity conservation programmes in these endangered endemic allopatric killifish populations, from the major southernmost unsampled areas of the Neotropical basins. Abstract : In this work, we characterize the morphological and genetic patterns of variability in taxa of the annual killifish of the Austrolebias robustus species group distributed in South America. While mitochondrial Cytb gene analyses detected four major clades which do not fully correspond to currently known species of the group, high level of overlap was detected in all morphological analyses. Our results highlighted that vicariance played a preponderant role, in the origin of highly endemic allopatric taxa in the Pampas grasslands.